Effect of Corporate Social Responsibility Disclosure to the Value of Companies With Environmental Management As a Moderating Variable - KAWISANA, Putu Gede Wisnu Permana; JAYANTI, Sri Eka; PERTIWI, Dewa Ayu Eka (PT Keberlanjutan Strategis Indonesia, 2023)
In today's modern era, competition in the business world is getting faster and more competitive. It can be seen on the Indonesia Stock Exchange which every year becomes the media for company entry and exit. This has resulted in companies competing to show the advantages that exist in each company to get good value in the eyes of investors. This study aims to determine and analyze the effect of CSR on firm value. So there is a need for further research related to the effect of the issuance of these regulations. It is hoped that this research can provide empirical evidence of the effect of CSR on company value, by including Environmental Management as a moderating variable. This research is a quantitative study using secondary data, namely in the form of sustainability reports from mining companies for 2019-2021. Testing the data using Moderation regression analysis. Results The type of data used in this study is quantitative data. The data source used in this research is secondary data with purposive sampling method. There are 3 variables studied, namely CSR disclosure, corporate values and environmental management. The results of this study obtained 45 research samples from 15 mining companies for the 2019-2021 period, and succeeded in proving that the CSR variable did not have a significant effect on company value, while the environmental management moderation variable was able to moderate strengthen the relationship between CSR and company value.